ANALISIS KESALAHAN BAHASA PADA TEKS CERAMAH SISWA SEKOLAH MENENGAH KEJURUAN - Stevania, Arinta Ayu; Wardani, Nugraheni Eko; Andayani, Andayani (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This research aims to describe: (1) a variety of a language error in Indonesia text lectures students (2) the factors cause the occurrence of an error in the text of the lecture, and (3) efforts that can be made to address errors in the text of the lecture Indonesia students of class XI SMK Murni 1 Surakarta 2018/2019 school year. This type of research is qualitative research. The technique of sampling with purposive sampling and in-dept interview Researchers using interactive analysis techniques, with the primary data source text lectures students of class XI SMK Murni 1. Theory triangulation technique is used as a test of the validity of the data. The results of the analysis of the findings of language errors in the text of the lecture differentiated by linguistic taxonomy can be explained as follows. First, the language errors are found in the text of the lecture students of class XI can be divided into four, namely the fault of 4.58% morphology, 5.15% of semantics, 6.10% of syntax and spelling of 84.35%. Second, the error-speaking students due to several factors, including: (a) unfamiliarity and lack of carelessness students in writing a text, (b) the limited sources of student learning, and (c) the lack of sensitivity of the student on the development of the language. Third, efforts to minimize the mistakes that language can do, including: (a) assessment of the student's writing, (b) add the learning resources, and (c) literacy and writing exercise for students.